Dinâmica do banco de sementes de arroz vermelho e ciclagem de nutrientes em função do manejo pós colheita da palha do arroz - Massoni, Paulo Fabricio Sachet (2011)
The incorporation of straw after the rice harvest in areas with the presence of red rice makes it difficult to reduce this weed in the seeds hank. On the other hand, it cilitates the straw's decomposition and advance the preparation of the area, which allows the sowing in the recommended period. The aim of this study was to evaluate the effect of soil tillage after harvest in cultivated areas with rice in reducing the viability of red rice seeds, as in decomposition of stubble, and nutrients losses. Treatments were arranged in a factorial design: the first factor was composed of [I] Standing water level,[2]straw incorporation with dry tillage soon after harvest, [3] straw incorporation with soil preparation flooded after harvest,[4]straw incorporation with dry soil only in July, [5] straw incorporation with soaked soil immediately after harvest and disking the area in July with dry soil, [6] straw incorporation with dry soil soon after harvest and disking of the area in July with dry soil, [7]without incorporation. The B factor was composed by different sampling dates. The experimental design of blocks was performed at random, with split plot with four replications. The maintenance of the water level and the lack of soil preparation reduced dormancy and viability over time for those seeds that remained on the soil surface. The after harvest soil preparation in flooded area showed significant reduction in dormancy, besides stimulating germination and impracticability of seeds, and It also allowed the early soil preparation for rice sowing. The lowest and highest straw decomposition occurred in treatment with maintenance of the irrigation water and soaked soil with preparation, respectively. The treatments that kept the straw on the surface presented a higher percentage of phosphorus remaining in the straw. Over 90% of potassium was released until41 days after harvest.There was no significant increase in nitrogen, phosphorus and potassium concentration in the soil at the end of the study period. None of the treatments used were effective in reducing the seed bank, nutrients loss and increasing straw decomposition at the same time.